Inflection and stability points of diphasic logistic analysis of growth - Mischan, Martha Maria [UNESP]; Souza Passos, Jose Raimundo de [UNESP]; Pinho, Sheila Zambello de [UNESP]; Carvalho, Lidia Raquel de [UNESP] (Univ Sao Paolo, 2015)
Growth functions with inflection points following a diphasic model, can be adjusted by two approaches using segmented regression or the sum of two functions. In both cases, there are two functions, one for each phase, with inflection and stability points. However, when they are summed, the result is a new function and the points of inflection and stability are different from those obtained from using each function individually. A method to determine these points in a diphasic logistics sum of functions is suggested and the results obtained from fitting the models to eucalyptus growth data showed a better fit of the logistic diphasic sum as compared with segmented regression and monophasic logistic models.
Keywords: Nonlinear models; Segmented regression; Sum of logistics